Perceived Quality of Life of Adolescents living in Slums of Uttar Pradesh, India. (January 2020) - Chauhan, Satish Kumar; Chauhan, Bal Govind; Jungari, Suresh; Dhar, Murali
Highlights: Adolescence refers to the transitional stage between childhood to adulthood. The study assess the quality of life (QoL) among adolescent residing in slums. The quality of life WHOQoL-BREF questionnaire has been utilised. Mean score of QOL was higher for social domains and least for environmental domain. Educational, wealth and type of house are the main determinants of QoL. The result indicates the urgent need for community-based intervention. Abstract: Adolescence is a transitional phase from childhood to independent adulthood, and it is often observed as a phase with heightened risk for future positive development. The current study assess the quality of life (QoL) among adolescent residing in slums. Primary data from 590 adolescents were collected from Lucknow district, Uttar Pradesh using multistage random sampling. For assessing the quality of life WHOQoL-BREF questionnaire has been utilised. The mean score of QoL was higher for social relation domains (68.1 ± 14.2) and least for the environmental domain of QoL (45.0 ± 12.0). The multivariate result shows that sex of the adolescent, marital status, education status, household economic status and type of house are the major determinant of quality of life (QoL) among adolescents living slums. A high level of poor QoL among adolescent calls for urgent community-based intervention for focused should be given to adolescents and household having more risk for the poor quality of life.